The impact of the COVID-19 pandemic on consumer and business confidence indicators - Deimante Teresiene; Greta Keliuotyte-Staniuleniene; Yiyi Liao; Rasa Kanapickiene; Ruihui Pu; Siyan Hu; Xiao-Guang Yue (Journal of Risk and Financial Management, 2021)
The COVID-19 pandemic and induced economic and social constraints have significantly impacted the confidence of both consumers and businesses. Despite that, comprehensive studies of the impact of the COVID-19 pandemic on the consumer and business sentiment are still lacking. Thus, in our research we aim to identify consumer and business confidence indicators' reaction to the spread of the COVID-19 pandemic in the Eurozone, the United States, and China. For this purpose, we used the method of correlation-regression analysis. We chose the consumer-confidence index, manufacturing purchasing manager's index, and services purchasing manager's index as dependent variables; and the number of confirmed cases of COVID-19, the number of deaths caused by COVID-19, and the mortality rate of COVID-19 infections as independent variables. The results showed a relatively rapid and robust effect of COVID-19 in the short period, but longer-term results depended on the region and were not so unambiguous: in the case of the Eurozone, the spread of COVID-19 pandemic did not affect the consumer-confidence index (CCI) or, in the cases of the United States and China, affected this index negatively; the purchasing managers' index (PMI) in the services sector was significantly negatively affected by the mortality risk of COVID-19 infection; and the impact on the purchasing managers' index (PMI) in the manufacturing industry appeared to be mixed.
Keywords: 330; COVID-19 pandemic; consumer confidence; economic sentiment; leading indicators